Jurisdiction Overview Implementation of Registration of Property Rights Transfer to Land by Grants - Pramudya Hutama (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
This research described and studied the freehold ownership of land transition by grant. This research is categorized as an empirical law research using the descriptive approach. This research is condusted in Kebumen Regency. There are two kinds of data that is used in this research, namely primary and secondary data. The method that is used in data collection are observation, interview, and library research based on Indonesia Law and Rules books, related documents, etc according to the topic. Data analysis using qualitative analysis by interactive model. The result of this research shows that the freehold ownership of land transition by grant in Kebumen Regency is already appropiate to the procedure in exist regulations. The freehold ownership of land transition by grant has to be registered in Kebumen Palace and National Land Office to gain certain law in the shape of title holder. Therefore the land status will be clear, it is not only about the burdens, the widht, but also the rights that in herent to it.